2015
DOI: 10.1177/1749975515584081
|View full text |Cite
|
Sign up to set email alerts
|

The Meanings of Discounts in Contemporary Art Markets: The Case of India

Abstract: Although discounts in art markets are commonplace, the phenomenon remains largely unresearched. This paper looks at how art market actors understand the functions of discounts, focusing on 'suppliers' of the market and drawing on qualitative interviews with artists and art dealers from New Delhi and Mumbai, conducted in January-April 2013. The theoretical basis of this paper is a cultural sociological stance on the functioning of markets, showing how a shared system of norms and values affects the operation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…While both art markets observed rapid development and international interest in the early 1990s, in Russia it has slowly evaporated, while the Indian art market continued with a steady rise, resulting in an impressive investment boom in the mid-2000s. Hit by the financial crisis, the Indian contemporary art market bubble has in the meantime burst and has not yet returned to the pre-crisis volumes of sales and levels of prices (see Komarova 2015). Nevertheless, the Indian market still seems to be more stable and sizeable than the Russian one.…”
Section: Activation Mechanisms and Market Performancementioning
confidence: 99%
“…While both art markets observed rapid development and international interest in the early 1990s, in Russia it has slowly evaporated, while the Indian art market continued with a steady rise, resulting in an impressive investment boom in the mid-2000s. Hit by the financial crisis, the Indian contemporary art market bubble has in the meantime burst and has not yet returned to the pre-crisis volumes of sales and levels of prices (see Komarova 2015). Nevertheless, the Indian market still seems to be more stable and sizeable than the Russian one.…”
Section: Activation Mechanisms and Market Performancementioning
confidence: 99%
“…Our study of the Chinese market, of which there is currently scant sociological research, shows, however, that its valuation practices and judgment devices differ from established markets in Europe and the USA (Moulin, 1987;Velthuis, 2005;Horowitz, 2011) as well as from other emerging art markets (see e.g. Favell, 2011;Brandellero, 2015;Komarova, 2015). In particular, our in-depth fieldwork has revealed that auction houses are ubiquitous in the Chinese contemporary art world, and appear in contexts where their presence would be considered illegitimate in other countries (Horowitz, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…In the literature, there are several researchers studying the assessment of artwork value from a sociological perspective. For example, Leahy (2009), Preece (2014), Komarova (2015), Khaire and Wadhwani (2010), Herrero (2011), Bonus and Ronte (1997), Velthuis (2003), Hutter and Throsby (2007), Sullivan and Butler (2017), Ağlargöz and Öztürk (2015), and Beteş (2016) consider the valuation and pricing of an artwork as a socio‐cultural process, occuring among sellers and buyers, and thus, focus on the analysis of the relationships and discourses among artists, gallery/auction house owners and collectors/investors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%